HUBUNGAN MONEY ATTITUDE DAN COMPULSIVE BUYING PADA PERILAKU BERBELANJA MAHASISWA TERHADAP BARANG FASHION YANG TERGOLONG FASHION BRANDED DENGAN COGNITIVE DISSONANCE AFTER PURCHASE SEBAGAI VARIABEL MODERATOR - Made Juliana Suksma W.; Laurentia Verina Halim S.; Ananta Yudiarso (CALYPTRA, 2018)
This study aims to see the role of cognitive dissonance after purchase as a moderator relationship between money attitude and compulsive buying on the behavior of the students shopping for fashion items classified as fashion branded. The result of this research is (1) money attitude is positively related to compulsive buying (r = 0.285; p-value = ≤ 0.05), these results explain that the personality determines the consumer's shopping behavior. The low correlation coefficient indicates that there are other factors that affect compulsive buying. (2) cognitive dissonance after purchase does not play a role model in the relationship between money attitude and compulsive buying, the result implies cognitive dissonance after Purchase fails to reinforce the relationship between money attitude and compulsive buying. It also shows that consumers who enter early adulthood are able to control their thinking and behavior after shopping